From Farm to Slaughter: Tracing Antimicrobial Resistance in a Poultry Short Food Chain - Andrea Laconi; Roberta Tolosi; Claudia Chirollo; Cristiana Penon; Giacomo Berto; Francesco Galuppo; Alessandra Piccirillo (Antibiotics)
Background: Short food supply chains are commonly perceived as more sustainable and safer alternatives to conventional production systems, often linked to organic, free-range livestock practices. Materials and methods: This study investigates, for the first time, the distribution of antimicrobial resistance genes (ARGs) and characterizes the microbial communities’ composition, using 16S rRNA sequencing and real-time PCR, respectively. Eleven fecal, 76 slaughterhouse surface, 11 cecal, and 11 carcass samples, from 11 poultry farms belonging to the same short food chain, were analyzed in the study. Results: While cleaning and disinfection procedures appeared to reduce the bacterial load on slaughterhouse surfaces, diverse and potentially resistant bacteria, including genera such as Staphylococcus and Streptococcus, persisted both before and after slaughter. ARGs conferring resistance to high-priority critically important antimicrobials (HPCIAs), such as fluoroquinolones and third-generation cephalosporins, were frequently detected on carcasses, with qnrS (76.15%, 95%CI 68.02-84.28%) and blaCMY2 (57.8%, 95%CI 48.38-67.22%) being the most prevalent. The slaughtering process emerged as a critical step for ARG dissemination via intestinal bacteria, such as genus Lactobacillus. Additionally, the detection of mcr genes and blaNDM on carcasses but not in the bird gut samples suggests possible anthropogenic contamination. Discussion: These findings highlight that the evisceration process, slaughterhouse environment, and personnel are all contributing factors in ARG spread and underscore the need for enhanced hygiene protocols and reduced gut ARG carriage in domestic birds to mitigate the risk for the consumer.